Impact of Consumer Empowerment on Satisfaction in an Online Brand Community: Mediating role of the Online Experience Toward the Brand - Ben Ameur, Habiba; Ben Rached , Kaouther Saeid (International Review of Management and Marketing, 2022)
In a connected world, the consumer has become an actor, informed and has access to all types of information. He can express his opinions, his experiences and seeks to acquire more control and power, which gives him meaning in his consumption (Moussafir and Qmichchou, 2021). According to Pruche (2014), consumer empowerment is associated more particularly with the development of e-commerce, which not only allows access to information but also facilitates the comparison of offers and makes the consumer more autonomous in its decision-making process. Through this academic work, we sought to know the relationship between consumer empowerment and satisfaction while specifying the role of the online experience towards the brand. The results of a survey carried out among 300 Tunisian Internet users subscribed to the online brand community "Mabrouk" reveal that the relationship between empowerment-satisfaction and online empowerment-experience towards the brand is significant, while the relationship between online experience and satisfaction is not significant.